Source of contamination and assessment of potential health risks of potentially toxic metal(loid)s in agricultural soil from Al Lith, Saudi Arabia - Alharbi Talal; El-Sorogy Abdelbaset S.; Al-Kahtany Khaled; Al-Hashim Mansour H. (Open Geosciences)
This study investigates the source, environmental impact, and health risks of potentially toxic metal(loid)s (PTMs) in agricultural soil from the Al Lith area along the Red Sea coast in Saudi Arabia. Soil samples were collected from 25 farms and analyzed using inductively coupled plasma–atomic emission spectrometry. Various indices were used to assess the contamination of the samples. Most soil samples belonged to Entisols, specifically Torripsamment, Torrifluvent, and Udipsamment subtypes. It was found that the average concentrations of PTMs follow the order of Zn (43.69) > Cu (21.69) > Ni (18.92) > Co (10.12) > Pb (2.62) > As (1.67). The average values of contamination indices indicated minor enrichment, low contamination, and low risk for all PTMs, with minor enrichment observed in some individual samples. The higher levels of PTMs in soil samples were reported from areas surrounding the Wadi Al Lith mouth. Multivariate statistics suggested that the primary source of PTMs in Al Lith soil was geogenic, derived from the weathering of basement rocks of the Arabian Shield. The mean hazard index (HI) values for humans (adults and children) followed the order of As > Ni > Pb > Cu > Co > Zn. The collective HI for PTMs in the Al Lith soil stayed below 1.0, indicating a non-carcinogenic risk. Additionally, lifetime cancer risk values for humans were lower than 1 × 10−4, indicating an acceptable or tolerable level of carcinogenic risk and suggesting negligible health hazards.